Identification and Description of Aquatic Oligochaeta in Sanggau City Canal West Kalimantan - Galuh Ramadhanti (bionature, 2023)
The canals in the center of Sanggau City, West Kalimantan serve as a medium for wastewater which enters the Kapuas River. The density of community activities in this city has caused indications of its canals being polluted by organic and inorganic materials. These contaminants enter the canal continuously, hence its accumulation can change the texture of the substrate/sediment which is the habitat for aquatic Oligochaete. The purpose of this study was to identify and describe the types of aquatic Oligochaete in the canals of Sanggau City. The research was conducted from August to September 2020 using the purposive sampling method at five stations, namely Tanjung Sekayam Village, Ilir Kota Village, Beringin Village, and Bunut Village, with three replications at each sampling station. The results showed that aquatic Oligochaete at the canals of Sanggau City consisted of 1 order, 1 family, 2 genera, and 3 species with a total of 1367 individuals. The identified species are Branchiura sowerbyi, Limnodrilus claparedeianus, and Limnodrilus hoffmeisteri.Keywords: Species Identification, Aquatic Oligochaeta, Sanggau City Canal